The role of multi-detector CT (MDCT) in patients presented with non-traumatic acute abdominal conditions - Abd-Zaid Akool, Mohammed (Journal of the Faculty of Medicine Baghdad, 2016)
Background: Acute abdominal pain classically refers to pain within the abdomen that has been present for less than 7 days from the time of presentation. The use of CT scan in the evaluation of acute abdominal pain has increased to a large extent due to high accuracy of CT in the diagnosis of specific diseases like appendicitis and diverticulitis, especially with the use of multidetector CT scanners. It has been shown that the use of intravenous contrast media increases the diagnostic accuracy of CT scan examination, with a positive predictive value of 95% in the cases of acute appendicitis. The accuracy of CT scan imaging in patients with acute abdominal pain was not affected by the lack of entral contrast material. Objectives: To evaluate the real usefulness of multi-detector CT( MDCT) in non-traumatic acute abdomen, to determine the cause of acute abdomen in those with uncertain pathological diagnosis. Patients and methods: This prospective study had been conducted at Al-Sader medical city from the first of January to the first of September 2015. Our study includes all patients presented to the emergency department with non-traumatic acute abdominal conditions with uncertain underlying cause inspite of detailed history and physical examination with negative or non-conclusive U/S, plain abdominal XR finding and the surgeon failed to identify the exact underlying pathology. This study included (80) patients, (44 male and 36 female) . Non-enhanced CT scan was done first for all patients which was sufficient to reach the diagnosis in (22) patients, contrast material were not used because blood urea was elevated in (6) patients . In (8) patients, CT angiography protocol was performed for patients with suspected mesenteric vessels pathology. In the remaining (44) patients, intravenous contrast was given manually via a wide bore cannula ( gauge 18) and post contrast scan done in the portal phase (delay time 45-50 second). Results: In this study, which was performed on (80) patients with undiagnosed nontraumatic acute abdominal conditions. We found that acute pancreatitis (20 patients)(25%) was the most common cause of undiagnosed acute abdominal pain, followed by intestinal obstruction (12 patients)(15%).While acute cholecystitis (8 patients)(10%) , portal or mesenteric vein thrombosis (8 patients ) (10%) , perforated viscus ,(6 patients)(7.5%), mesenteric arterial thrombosis (4 patients) (5%) ,left gastric artery aneurysm (2patient))(2.5%) , acute appendicitis(2 patient ) (2.5%)diverticulitis (2patient) (2.5%) and ectopic pregnancy (2patient) (2.5%). In (14 patients) (17.5%), no specific pathology could be detected. Conclusion: The role of multi-detector CT (MDCT) has an important role in the management undiagnosed acute abdominal conditions in the emergency department. Acute pancreatitis is one of the main cause of undiagnosed acute abdominal conditions.